Empagliflozin Alleviates Left Ventricle Hypertrophy in High-Fat-Fed Mice by Modulating Renin Angiotensin Pathway - Cotrin, Juliana Cordovil; de Souza, Gabriel Santos Martins; Petito-da-Silva, Tamiris Ingrid; Cardoso, Luiz Eduardo Macedo; Souza-Mello, Vanessa; Barbosa-da-Silva, Sandra (Journal of the Renin-Angiotensin-Aldosterone System, 2022)
Aims. The cardiobenefits of empagliflozin are multidimensional, and some mechanisms are still unclear. The aim of the present study was to evaluate the effect of treatment with empagliflozin on biometric parameters and gene expression in the local cardiac RAS, oxidative stress, and endoplasmic reticulum pathways in a mouse model. Main Methods. Forty male C57BL/6 mice were fed with control (C) or high-fat (HF) diets for 10 weeks. After that, the groups were redistributed according to the treatment with empagliflozin—CE or HFE. The empagliflozin was administered via food for 5 weeks (10 mg/kg/day). We performed biochemical analyses, blood pressure monitoring, oral glucose tolerance test, left ventricle (LV) stereology, RT-qPCR for genes related to classical and counterregulatory local RAS, oxidative stress, and endoplasmic reticulum stress. Key Findings. In comparison to HF, HFE decreased body mass and improved glucose intolerance and insulin resistance. The cardiac parameters were enhanced after treatment as expressed by decrease in plasma cholesterol, plasma uric acid, and systolic blood pressure. In addition, LV analysis showed that empagliflozin reduces cardiomyocyte area and LV thickness. The local RAS had less activity of the classical pathway and positive effects on the counterregulatory pathway. Empagliflozin treatment also decreased oxidative stress and endoplasmic reticulum stress-related genes. Significance. Our results suggests that empagliflozin modulates the local RAS pathway towards alleviation of oxidative stress and ER stress in the LV, which may be a route to its effects on improved cardiac remodeling.